Elevation of C-reactive protein during the luteal phase in healthy adolescents. (April 2015) - Merino, Paulina M.; Martínez, Daniela; Iñiguez, German; Lopez, Patricia; Cassorla, Fernando; Perez-Bravo, Francisco; Codner, Ethel
Abstract Introduction: Variations in inflammatory markers have been reported in adult women during the luteal phase, but whether these findings are observed during adolescence is unknown. We postulate that higher ultrasensitive C-reactive protein (usCRP) and lower 2-hydroxyestrone (2OHE) levels, an estrogen metabolite with cardioprotective actions, are present during the luteal phase in young women. Aim: To evaluate usCRP levels during the menstrual cycle and to determine its association with 2OHE and 16α-hydroxyestrone (16OHE) in adolescents. Methods: Healthy postmenarcheal adolescents (N = 37) were studied during one menstrual cycle in follicular phase (FP) and luteal phase-like period (LP-L). Results: Elevations in usCRP levels in the LP-L were observed in the entire group and in anovulatory cycles (1.9 ± 1.1 mg/L in FP to 2.5 ± 1.8 mg/L in LP-L; p < 0.0001). Increases in estrone, estradiol, free and bioavailable estradiol, testosterone, usCRP and 2OHE levels were observed in LP-L compared with FP (p < 0.01), with a borderline elevation in IFG-I levels (p = 0.06). Conclusions: We report an elevation of usCRP and 2OHE levels during the luteal phase in healthy adolescents. Elevations of this inflammatory marker in anovulatory adolescents without an increase in 2OHE may play a role in metabolic risks associated with chronic anovulation.